Growing up in the west: county report Roscommon. (WRDATF, 2019)
Planet Youth is an international evidence-based primary prevention model, developed in Iceland, that has been used to reduce substance use rates amongst adolescents. The model’s whole population approach offers an opportunity to improve public health outcomes in many areas. It works by directly targeting the risk and protective factors in young people’s lives that determine their substance use behaviours and enhancing the social environment they are growing up in. By developing targeted interventions that seek to reduce the identified risk factors and strengthen the identified protective factors the problems associated with adolescent substance use can be reduced or prevented before they arise. In October 2018 all of the pupils in Roscommon that returned to school after sitting the Junior Certificate were invited to complete the Planet Youth questionnaire. This report summarises the findings from the 9 schools and 2 Youthreach centres in the county and comprises 480 respondents.